UAV RGB image encryption based on DNA coding algorithm and row and column interleaving - Tejada-Begazo, Maria; Chacón, Christina (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
The use of unmanned aerial robots has increased, especially in inspection. Therefore, image security must be considered, something essential for companies that use these robots. This reason made us devise a way to encrypt these images for sending. Our proposal involves a unique combination of DNA, the interleaving of rows and columns, and a cryptography technique. This technique generates a key, which is then used in the encryption process. The interleaving of rows and columns is used to shuffle the image data, adding an extra layer of security. Several tests were carried out, and the performance of our proposal was good, and the decryption of the images was the same as the original. The cryptography techniques that were tested were RSA and ECC. The best result with the “Lenna” image was an entropy of 7.6 for both techniques, and the correlation between the original and encrypted image corresponded to 0.01 with RSA and 0.05 with ECC.